Implementasi Bimbingan dan Konseling dalam Menanggulangi Kasus Pacaran di Kelas IX Sekolah MTS Al-Mubarak, Marisa Kab. Pohuwato - Muh Wahyuddin S Adam; Sri Uzlifatul Zannah Ali; Munifatul Azmi Bagi (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
Teenage dating in schools is a major problem that affects various things, such as academic achievement, social relationships, and emotional well-being of students. This study investigated the use of guidance and counseling services in dealing with cases of teenage dating in schools. This study was conducted through a descriptive qualitative approach and used interviews, observations, and documentation as data collection methods. This study involved BK teachers, homeroom teachers, and grade IX students who were identified as being involved in dating behavior at MTS Al Mubarak. The results showed that BK teachers played an important role in various efforts, such as providing information, offering individual counseling, holding group discussions, and working with parents. These efforts succeeded in supporting healthy relationship management and increasing students' awareness of the negative impacts of dating. These results show the importance of preventive counseling and intervention in.